2021
DOI: 10.48077/scihor.24(5).2021.92-107
|View full text |Cite
|
Sign up to set email alerts
|

Foreign-Economic Priorities of the Development of Investment Infrastructure of Agri-Food Production Entities

Abstract: The article considers foreign economic priorities of investment infrastructure development of agri-food production entities of Ukraine. A comprehensive methodological approach to assessing the effective diversification of investment infrastructure of agri-food production entities has been developed. It is substantiated diagnostics of attracting foreign direct investment in the development of agri-food production allows forming an export-oriented type of state economy, identify the main sources of technical equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Further research can be aimed at developing longer-term programs for the use of drones and virtual reality in the educational process of students from the first year of study and for students of different specialties. Earlier studies on the value of virtual reality learning environments show an increase in the number of learning environments that use virtual reality specifically for certain specialties such as agronomy and agriculture, geography, and ecology [73], [74], [75], [76], [77]. This study has revealed the effectiveness of VR and drones in the fields of IT technology, architecture and urban planning, engineering, robotics, and journalism.…”
Section: Discussionmentioning
confidence: 84%
“…Further research can be aimed at developing longer-term programs for the use of drones and virtual reality in the educational process of students from the first year of study and for students of different specialties. Earlier studies on the value of virtual reality learning environments show an increase in the number of learning environments that use virtual reality specifically for certain specialties such as agronomy and agriculture, geography, and ecology [73], [74], [75], [76], [77]. This study has revealed the effectiveness of VR and drones in the fields of IT technology, architecture and urban planning, engineering, robotics, and journalism.…”
Section: Discussionmentioning
confidence: 84%
“…By developing the agricultural industry, it is possible to substantially improve the situation not only in the Sakha Republic, but also to increase the level of self-sufficiency in food throughout Russia (Table 2). This can be done by developing and forming new economic relations, creating methods for regulating processes in the agro-industrial complex, as well as in its components, and investing in the development of rural regions (Trusova et al, 2021). Such a policy should be positioned not only as the protection of national security, but also as a socio-economic one, which will hold not only the state authorities, but also representatives of local government, businessmen, scientists, and the rural population accountable for its success and ensuring a high quality of life for people.…”
Section: Resultsmentioning
confidence: 99%
“…This basis is supplemented by variable criteria of a distributive nature, according to the norms and rules of cooperation of agro-food production entities in public-private partnership, which modify the methods of evaluating the sources of investment flows to activate the platform of investment opportunities, which have an impact on the permanent nature of the investment process. That is, in the structure of the institutional matrix of public-private partnership, the platform of investment opportunities of subjects of agro-food production is formed with the help of a set of sources of investment flow, capable of attracting, accumulating, distributing and using them, which ensure the investment activity of subjects of agro-food production (Trusova et al, 2021b;Vorsovskyi, 2007) (Fig. 1).…”
Section: Sources Of the Investment Flow For The Restoration Of The In...mentioning
confidence: 99%